The relationship between the efficacy of methotrexate in rheumatoid arthritis and the achieved level of its polyglutamates in erythrocytes (pilot study) - G. I. Gridneva; Yu. V. Muravyev; N. V. Demidova; E. S. Aronova; A. V. Pivanova; M. A. Borisova; S. I. Glukhova; A. S. Starkova; N. M. Savushkina; S. O. Krasnenko; K. S. Nurbaeva; N. V. Baimeeva; et al. (Научно-практическая ревматология)
Therapeutic control of the methotrexate (MT) polyglutamates (MTPG) level in erythrocytes can be an objective marker of the effective dose of MT prescribed for rheumatoid arthritis (RA).Objective: to assess the relationship between the level of MTPG in red blood cells and efficacy of the MT dose used by RA patients.Subjects and methods. The study included 60 patients with RA (44 women and 16 men over 18 years) who met the criteria of the American College of Rheumatology and the European League Against Rheumatism (ACR/EULAR) 2010 and received MT ≥20 mg/week subcutaneously for ≥12 weeks. The patients were divided into two groups of comparable age, sex, alcohol intake, number of smokers, body mass index (BMI), depending on the presence (group 1; n=30) or absence (group 2; n=30) of the effect of MT, according to the EULAR efficacy criteria (DAS28). The concentration of MTPG (total MTPG and metabolites of MTPG 1, 2, 3, 4, 5) was determined in erythrocytes by high-performance liquid chromatography with mass spectrometric detection.Results and discussion. It was found that the levels of total MTPG and MTPG1, 2, 3, 5 in erythrocytes did not differ in groups of responders and nonresponders, and the dose of MT was comparable in both groups. At the same time, the level of MTPG4 in the first group was significantly higher (26.4±6.1 nmol/l; p=0.023) than in the second one (22.1±6.8 nmol/l). Analysis of the ROC curve showed that the values of MTPG4 <22.5 nmol/l corresponded to the absence of effect of MT. The area under the curve was 0.672 (95% confidence interval 0.536–0.808 (p=0.022), sensitivity 77%, specificity 53.3%.Conclusion. For effective treatment of patients with RA MT dose should provide MTPG4 level in red blood cells ≥22.5 nmol/l.